(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background: calcifications may be physiological or pathological. Understanding about soft tissue calcifications help to reach appropriate diagnosis and take the right decision whether treatment, referral, further investigations or do nothing. Aim: To detect the prevalence of soft tissue calcifications using (CBCT) scans in the Egyptian population. Method: Retrospective Data Analysis was performed on (417) CBCT patients’ scans collected from the database available at the Oral & Maxillofacial Radiology department,Faculty of Dentistry, Cairo University. Data collection of patient sex and age was made. Data was assessed for presence or absence of calcification, type of calcification, sidedness and single or multiple occurring. Results: There were (94) scans detected with calcifications within the whole sample size (417 scans). The prevalence was (22.54%). There were (141) calcifications detected in the (94) scans. The soft tissue calcifications detected were calcified stylohyoid ligament, tonsilloliths, sialoliths, laryngeal cartilage calcification, carotid artery calcification and only one case of ethmoidal sinolith. There were 3 cases without certain final diagnosis. Conclusions: The prevalence of calcifications seen on CBCT images is not uncommon, dental practitioners should be aware of their presence. Their detection during routine dental examination should be made to ensure the broad evaluation of the patients.